RxBox 0.3 Triage interface, VoIP integration and GUI-MVC refactoring for the RxBox - Ebido, Timothy John; Soler, Thomas Rodinel (2010)
Telemedicine is the use if information and communication technologies to provide medical information and healthcare services. The key aspect of telemedicine is the use of electronic signals to transfer health information between two or more locations and to provide medical expertise and services to remote locations.Most rural and some urban areas in the Philippines have limited or no access to quality health services. One reason is that few doctors prefer to work in rural areas. The result is that most specialized doctors are concentrated around urban areas. One solution to this problem is the development of a local telemedicine system.RxBox, a component of the PCHRD's research program titled " National Telehealth Service", is a Linux-based telemedicine appliance that collects biomedical signals from the patient. On its second year, the project developed an interface between the RxBox and triage, using the Internet as the medium for communication. A database was developed to collect data from sessions, patient information, and medical signals before they are sent to triage. VoIp and instant messaging capability was integrated to the RxBox for real-time consultation.To improve the development efficiency of RxBox, Model-View-Controller (MVC) architecture was used to decouple the graphical user interface (GUI) modules from the data acquisition modules and other peripherals was developed for faster usability assessment and for possible use for education of medical personnel. The complete prototype of RxBox was tested in pilot sited around the country. Comments derived fromthe usability sessions and pilot tests were factored for the development of the RxBox.
Thesis (B.S. Electronics and Communications Engineering) -- University of the Philippines, Diliman
Keywords: Telecommunication in medicine -- Philippines; Internet telephony; Delivery of Health Care; Telemedicine -- Philippines; Medical telematics; RxBox; Model-View-Controller architecture; National Telehealth Service